Age‐specific reference ranges of serum anti‐müllerian hormone in healthy women and its application in diagnosis of polycystic ovary syndrome: a population study. (25th February 2020) - Li, HWR; He, Y‐L; Li, R; Wong, CYG; Sy, B; Lam, CW; Lam, KSL; Peng, H‐M; Mu, S; Schooling, M; Yeung, WSB; Ho, PC; et al.
Abstract : Objective: To establish the age‐specific centiles of serum anti‐müllerian hormone (AMH) levels in Chinese women, and to explore the use of multiples of median (MoM) AMH levels for the diagnosis of polycystic ovary syndrome (PCOS). Design: An observational study. Setting: University‐affiliated hospitals and community clinics. Population: We included 3137 healthy women aged 20–44 years recruited prospectively or who had archived serum samples from previous research projects. Another validation cohort of 751 women with PCOS as well as ovulatory controls, which was a convenient sample of women attending for infertility or menstrual disorders, was also studied. Methods: The serum samples were assayed for AMH by the automated Access AMH assay. Main outcome measures: Age‐specific reference ranges were constructed on the primary cohort with the Lambda‐Mu‐Sigma method. The MoM AMH of each subject in the validation cohort was calculated. Results: Centile curves of serum AMH level against age were established. MoM AMH was significantly higher in women with PCOS than in controls ( P  < 0.05). The area under the ROC curve was 0.852 (95% confidence interval [CI] 0.825–0.877) ( P  < 0.0001) for discriminating women with PCOS from ovulatory controls by MoM AMH. Conclusions: We established a set of year‐by‐year age‐specific reference ranges of serum AMH levels in Chinese women. The MoM AMH derived from this set of reference ranges is a promising tool to replace antral follicle count in the diagnosis of PCOS. Tweetable abstract: A set of age‐specific reference ranges of AMH levels was established in Chinese women. Multiples of median AMH may be used to diagnose PCOS. Tweetable abstract: A set of age‐specific reference ranges of AMH levels was established in Chinese women. Multiples of median AMH may be used to diagnose PCOS.